Perbandingan Kinerja Reksa Dana Syariah dengan Reksa Dana Konvensional - Cahyaningsih Cahyaningsih; Eko Suwardi; Doddy Setiawan (The Indonesian Journal of Accounting Research, 2013)
The objective of this research is to evaluate the balanced shariah mutual fund performance compared with the balanced conventional mutual fund performance during the bull market of 2004-2006. Mutual fund performance can be measured by using Jensen Index, Sharpe Index, Treynor Index, MM Index, and TT Index. The information about security selection and market timing ability can be measured by using Henriksson-Merton Model and Treynor-Mazuy Model. The statistic methods used to test hypothesis are one sample t-test, independent sample t-test, simple regression analysis, and multiple regression analysis. Finally, the results show that during the bull market of 2004 and 2006 the conventional mutual funds have been able to outperform the shariah mutual funds, but in 2005 the shariah mutual funds have been able to outperform the conventional mutual funds. Portofolio managers of the conventional mutual funds have superiority skills in security selection and market timing ability than portofolio managers of the shariah mutual funds.